THU0743-HPR A new and alternative treatment in sclerodermic digital ulcers. (15th June 2017) - Muratore, M; Carati, D; Quarta, L; Grimaldi, A; Quarta, E; Garzya, M; Longo, D; Casilli, O; Calcagnile, F
Abstract : Background: Digital ulcers (DUs) are a major clinical problem for patients with systemic sclerosis (SSc). Patients with DUs may suffer from severe pain and often undergo a limitation of daily life activities, thus resulting in a functional impairment with a significant impact on the patient's health-related quality of life. Prevention of further complications and lesions is possible if the initial evaluation is performed early and correctly and if a treatment is started promptly. Objectives: The primary objective is to demonstrate the effect of Lecoxen cream (Ekuberg Pharma, Italy) in comparison with another cream (Fitostimoline cream, DAMOR SpA, Italy) on the reduction of the number and size of DUs in patients with systemic sclerosis evaluating in addiction the reduction of pain dealing with DUs and quality of life. Methods: In this single-blind randomized progressive trial 39 women, with confirmed digital ulcers present for at least 4 weeks with a surface area greater than 0.5 cm 2 but smaller than 2, 5 cm 2, that follow Iloprost therapy (0, 05mg/2 times/month), afferent to the Operative Unit (O.U.) of Rheumatology of the Local Health Unit (LHU) of San Cesario di Lecce, were randomized to receive the topical application of Lecoxen cream (group I: 20 women) or Fitostimoline cream (group II: 19 women). We took digital photographs to measure ulcer surface area and to draw the periwound area before the first cream application and after 30 days. Then an evaluation of DUs diameter and number was carried out. A tailored questionnaire was administered as Visual Analogue Scale (VAS) during monitoring visits, to evaluate intensity of pain. Furthermore quality of life was monitored through Short Form (36) Health Survey. Results: Mean age was similar in the two study groups with values of 45.4±5.6 years and 46.1±4.1 respectively. In the patients treated with Lecoxen cream, the reduction of lesion size was significantly higher (70%–75%) (p<0, 001) in comparison with those registered in group II (40–45%) (p<0, 05); a significant improvement was observed in levels of pain in Group I (30 days: p<0, 001), while in group II the results of reduction were not significant. The analysis of SF36 survey showed highly significant reduction (p<0, 001) of indexes in group I. At last visit, 32 ulcers were healed: 17 in the group I (p<0, 001), 11 in the Group II (p<0, 01). Two-way analysis of variance (ANOVA) test was used to examine differences. Intragroup changes were evaluated with the paired Student t-test. A p-value of <0.05 was considered to be significant. Conclusions: Lecoxen cream showed the greatest effect on the mean reduction of the lesion size and pain levels. In the patients treated with Lecoxen cream the reduction of lesion size was 70%–75%; the reduction was smaller in the group II. At last visit, 32 ulcers were healed: 17 in the group I, 11 in the Group II. Data collected from SF36 surveys are very interesting, because they show a clear improvement in quality of life of scleroderma patients, who underwent three different treatments. In particular, a better subjective perception of tactile sensation and minor discomfort in the pathological skin have been reported. On the basis of the results, it could be argued that the medical device Lecoxen cream may be useful in the treatment of DUs in patients suffering from systemic sclerosis. Disclosure of Interest: None declared